Research Progress on Photocatalysis of Lead-Free Halide Perovskite Cs3Bi2X9 (X=I, Br, Cl) - Mu, Benhong (International Journal of Materials Science and Technology Studies, 2026)
In recent years, the application of metal halide perovskites in the field of photocatalysis has emerged as a rapidly developing research area. However, the toxicity and stability issues of traditional lead (Pb)-containing perovskites limit their large-scale application. Therefore, the development of efficient and stable lead-free perovskite materials is one of the key current research directions. Cs3Bi2X9 (X = I, Br, Cl), as a lead-free metal halide perovskite, offers the primary advantages of being environmentally friendly and having potentially higher stability. This article provides an overview of the application of this material system in replacing lead-based perovskites to achieve environmentally friendly photocatalysis, as well as its synthesis methods. It aims to serve as a reference for the development of efficient and stable lead-free perovskite photocatalysts.